Exploring the association of natriuretic peptides with QTc interval in hemodialysis patients - Yoshihiro Matsumoto; Yasuo Mori; Shinji Kageyama; Kazuaki Yoshimura; Takao Saito; Risako Terada; Yohichi Nojima (Renal Failure)
Background In patients undergoing hemodialysis (HD), cardiovascular (CV) disease, particularly sudden cardiac death (SCD), is a major cause of mortality. Independent predictors of SCD include a prolonged QT interval on electrocardiography (ECG) and elevated levels of natriuretic peptides (NPs). This study explores the association between the QTc interval and NPs in HD patients.Methods This cross-sectional study involved 207 HD patients, having a heart rate of 57 to 103 bpm, displaying sinus rhythm and no extrasystoles in ECG reports. Before the 2nd HD of the week, we conducted ECG and blood tests for atrial NP (ANP), brain NP (BNP), and N-terminal proBNP (NT-proBNP). The heart rate-corrected QT (QTc) was calculated using Bazett formula. Our analysis focused on the association between QTc and each NP, along with evaluating clinically relevant variables related to the QTc interval.Results Univariate analyses indicated robust correlations among the NPs, with each NP significantly associated with the QTc interval. Multiple regression analyses of the three NPs revealed that NT-proBNP demonstrated the strongest predictive ability for the QTc interval. Independent predictors of prolonged QTc included lower corrected calcium (cCa) levels (p = 0.001), lower potassium (K) levels (p < 0.001), and higher log NT-proBNP (p = 0.004).Conclusion In HD patients, NT-proBNP shows a stronger link with the QTc interval than BNP or ANP. Integrating clinical management considering both QTc and log NT-proBNP levels might help reduce CV events. Additionally, vigilance regarding low K or cCa levels is recommended from the perspective of the QTc interval.